Rapid detection and identification of Dioscorea compounds in Dioscorea hispada tuber plants by LC-ESI-MS - Kamaruddin, Z. H.; Sapuan, S. M.; Mohamed Yusoff, M. Z.; Jumaidin, R. (North Carolina State University, 2020)
Studies have revealed that Dioscorea hispida tubers contain a poisonous substance called alkaloid dioscorine. The method for removing alkaloid dioscorine in Dioscorea hispida is explored in this research through a soaking process. The tubers were peeled, washed, sliced, and soaked for 5 days in either 1.0 M sodium chloride (NaCl) or distilled water. The aim of this study was to firstly identify the amount of toxic dioscorine remaining after soaking for 5 days, and then determine the best solution for removing dioscorine compounds in the tubers that were obtained from a tropical area in Peninsular Malaysia. The liquid chromatography electrospray ionization mass spectrometric (LC-ESI-MS) systems were used to identify the presence of alkaloid dioscorine compounds within Dioscorea hispida tubers. The analysis showed that no dioscorine compounds were present in day 5 for samples soaked in the NaCl solution. However, the relative abundance in the distilled water solution at day 5 was 281000, indicating a 95% decrease of the relative abundance value of the dioscorine compounds. This work aimed to determine the minimum days needed to remove the poisonous element before Dioscorea hispida tubers could be used for food consumption or for any other applications.